PENGAWASAN PERBANKAN SYARIAH UNTUK OPTIMALISASI GOOD CORPORATE GOVERNANCE MELALUI ISLAMIC CORPORATE IDENTITY - ., Isfandayani (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2012)
Growth and development of Islamic economics can be viewed through Islamic financial institutions including Islamic banking. Islamic banking can be said to grow and develop from the BUS, UUS, SDI, Assets, and Customer. Existing data in 2011, BUS numbered eleven, and the 1253 Branch. UUS totaled 23 with 280 branches. BPRS total 151 with 291 branches. Human resources (SDI) amounted to 21 368 people. Growth and positive development of Islamic banking should always be supervised to ensure that public confidence continues to increase and maintain the continuity of Islamic banks themselves. Supervision of a well-run will optimize the Good Corporate Governance (GCG). One reflection of good Corporate Governance can be seen from the transparency of financial statements in which there is Islamic Corporate Identity. This study limits the analysis only to the products and the supervision of Islamic Corporate Identity contained in the financial statements of Islamic banks in Indonesia. Object of research is on the financial statements 2011 and for ten BUS BNI Syariah in 2010. Through this research is expected the application of Islamic Corporate Identity note in the financial statements and the optimal realization. GCG getting better and people's confidence will grow if the Islamic banks can highlight and apply Islamic Corporate it Identity